Hypoxic vascular response and ventilation/perfusion matching in end-stage COPD may depend on p22phox. Issue 1 (20th July 2017) - Nagaraj, Chandran; Tabeling, Christoph; Nagy, Bence M.; Jain, Pritesh P.; Marsh, Leigh M.; Papp, Rita; Pienn, Michael; Witzenrath, Martin; Ghanim, Bahil; Klepetko, Walter; Weir, E. Kenneth; Heschl, Stefan; et al.
Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease in which the amount of emphysema and airway disease may be very different between individuals, even in end-stage disease. Emphysema formation may be linked to the involvement of the small pulmonary vessels. The NAPDH oxidase (Nox) family is emerging as a key disease-related factor in vascular diseases, but currently its role in hypoxia-induced pulmonary remodelling in COPD remains unclear. Here we investigate the role of p22phox, a regulatory subunit of Nox, in COPD lungs, hypoxic pulmonary vasoconstriction (HPV), hypoxia-induced pulmonary vascular remodelling and pulmonary hypertension. In COPD, compared to control lungs, p22phox expression was significantly reduced. The expression was correlated positively with mean pulmonary arterial pressure and oxygenation index and negatively with the diffusing capacity of the lung for carbon monoxide (p<0.02). This suggests a role of p22phox in ventilation/perfusion ratio matching, vascular remodelling and loss of perfused lung area. In p22phox -/- mice, HPV was significantly impaired. In the chronic hypoxic setting, lack of p22phox was associated with improved right ventricular function and decreased pulmonary vascular remodelling. p22phox-dependent Nox plays an important role in the COPD phenotype, by its action on phase II HPV and chronic vascular remodelling. In COPD, p22phox controls hypoxic pulmonary vascular response and ventilation–perfusion matching http://ow.ly/9Koo30aWMmT